Heterogeneity of Pharmacy Education in Europe - Jeffrey Atkinson (Pharmacy, 2014)
The 1985 European Economic Community (EEC) directive on the sectoral profession of pharmacy assumed that the comparability of pharmacy education across Europe could provide a basis for the mutual recognition of diplomas. A study by the European Association of Faculties of Pharmacy (EAFP) in 1994 showed, however, that there was large variability in course content. The 2011 PHARMINE study investigated whether such variability had decreased. Information from across the EU countries on the number of contact hours in specific subject areas was compared for the years of 1994 and 2011. Data was obtained from the original 1994 Bourlioux/EAFP study and the 2011 PHARMINE survey. As the latter was based on the 1994 survey, the questions and categories were similar. Results show that there has not been a fall in the variability of course content. Furthermore, EU pharmacy courses have become more “clinical” with an increase in contact hours in the subject area of medicinal sciences.